AUTISM SPECTRUM DISORDER AND CHILD COMMUNICATION: A SENSITIVE ANALYSIS - dos Passos, Thays Cristina Vieira Portes (Seven Editora, 2026)
Verbal communication is essential for social interaction and human expression. Children with Autism Spectrum Disorder (ASD) frequently face communicative difficulties, which can be exacerbated by motor aspects such as hypotonia. This article explores the influence of hypotonia on speech production in children with ASD, highlighting that, even without significant cognitive deficits in language acquisition, muscle weaknesses can compromise articulation and verbal fluency. Therapeutic interventions, such as occupational and speech therapy, and the importance of augmentative and alternative communication (AAC) methodologies, including Brazilian Sign Language (Libras), communication boards, and technological resources, are discussed. Jean Piaget's theory on the interrelationship between motor and cognitive skills in language acquisition is considered. The objective is to offer a comprehensive view of the challenges and strategies to improve communication in children with ASD, promoting social inclusion and opportunities for expression.